Evaluating a Technology-Based Assessment (TBA) to Measure Teachers' Action-Related and Reflective Skills - Zlatkin-Troitschanskaia, Olga; Kuhn, Christiane; Brückner, Sebastian; Leighton, Jacqueline P. (International journal of testing, 2019)
Teaching performance can be assessed validly only if the assessment involves an appropriate, authentic representation of real-life teaching practices. Different skills interact in coordinating teachers' actions in different classroom situations. Based on the evidence-centered design model, we developed a technology-based assessment framework that enables differentiation between two essential teaching actions: action-related skills and reflective skills. Action-related skills are necessary to handle specific subject-related situations during instruction. Reflective skills are necessary to prepare and evaluate specific situations in pre- and postinstructional phases. In this article, we present the newly developed technology-based assessment to validly measure teaching performance, and we discuss validity evidence from cognitive interviews with teachers (novices and experts) using the think-aloud method, which indicates that the test takers' respective mental processes when solving action-related skills tasks are consistent with the theoretically assumed knowledge and skill components and depend on the different levels of teaching expertise.